2014
DOI: 10.1016/j.jad.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Comfort from suicidal cognition in recurrently depressed patients

Abstract: BackgroundPrevious research has suggested that some individuals may obtain comfort from their suicidal cognitions.MethodThis study explored clinical variables associated with comfort from suicidal cognition using a newly developed 5 item measure in 217 patients with a history of recurrent depression and suicidality, of whom 98 were followed up to at least one relapse to depression and reported data on suicidal ideation during the follow-up phase.ResultsResults indicated that a minority of patients, around 15%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 18 publications
5
36
1
2
Order By: Relevance
“…Our findings were consistent with the literature connecting positive responses to MI with STBs (Crane et al., , ). This is consistent with escape‐based models of suicide, in general, and the positive feedback model of suicide (Katz et al., ; Yaseen et al., ), in particular.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings were consistent with the literature connecting positive responses to MI with STBs (Crane et al., , ). This is consistent with escape‐based models of suicide, in general, and the positive feedback model of suicide (Katz et al., ; Yaseen et al., ), in particular.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, even nonsuicide ideation was associated with SI with intent. These findings are consistent with Crane and colleagues’ (Crane et al., , ). The very high prevalence and clinical significance of MI suggest that much more attention should be paid to the phenomenon.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, using the Multi-Attitude Suicide Tendency scale (e.g., Ferrara, Terrinoni, & Williams, 2012;Muehlenkamp & Gutierrez, 2004;Orbach et al, 1991;Osman et al, 2000); by examining the comfort some individuals derive from suicidal ideation (Crane et al, 2014); and by comparing the desirability of life versus death (Brown, Steer, Henriques, & Beck, 2005;Kovacs & Beck, 1977). The current study therefore seeks to fill this gap in the literature by examining the validity of implicit evaluations of death.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that patients diagnosed with unipolar depression [5,7] or bipolar disorder [8,9] report repetitive intrusive suicide-related images and thoughts. These suicidal images may be both distressing and comforting [5,20], and can be seen as a last visualized escape to protect oneself against future adversity [21,22]. Examples include imagining oneself during or right after committing suicide (taking an overdose, jumping off a bridge), or visualizing the reaction of family members.…”
Section: Introductionmentioning
confidence: 99%